Integrated techno-economic analysis and life cycle assessment of emerging technologies with temporal resolution - Sproul, Evan, author; Quinn, Jason C., advisor; Marchese, Anthony J., committee member; Jathar, Shantanu H., committee member; Denning, A. Scott, committee member (Colorado State University. Libraries, 2020)
Techno-economic analysis (TEA) and life cycle assessment (LCA) are analytical tools used to quantify the economic and environmental performance of emerging technologies. TEA and LCA help guide the development of these technologies by identifying areas where additional research will significantly reduce economic costs and environmental impacts. Although often used in tandem, TEA and LCA output separate results that rely upon disconnected metrics. When considering the impact of time, the disconnect between TEA and LCA methods is critical and can significantly impact results. In this dissertation, three phases of research are conducted to illustrate and reconcile the disconnect between TEA and LCA. In the first phase, standard TEA and LCA methods are used to evaluate the economic and environmental performance of natural rubber derived from guayule (Parthenium argentatum). This evaluation is used to identify the strengths and weaknesses of interpreting disconnected TEA and LCA results. In the second phase, two new methods are created to overcome this disconnect by integrating temporally resolved TEA and LCA. These methods are applied to electric power and guayule rubber production to highlight the impacts of integrating temporally resolved TEA and LCA. In the third phase, integrated TEA and LCA is used to perform a deep-dive evaluation on low-emissions technology options for natural gas combined cycle power plants. In this phase, TEA and LCA with temporal resolution are used to identify cost targets for biomethane, carbon capture and storage (CCS), and bioenergy with CCS (BECCS) under different emissions pricing scenarios. Taken together, the three phases of research in this dissertation represent a wide range of applications and methodologies, each with varying objectives and complexity. Understanding the details of these approaches will help guide future analysis where economic costs, environmental impacts, and time are important considerations in technological development.
Keywords: greenhouse gas emissions; natural gas; sustainability; guayule; electricity generation; renewable energy